Protein for adaptations to exercise training - Tipton, K. D. (European Journal of Sport Science, 2008)
Nutrient intake before, during, and after training will influence the adaptations that occur in response to the training stimulus. The influence of protein on training adaptations is receiving increasing attention from researchers. Methodological issues should be carefully considered when evaluating evidence of nutritional influence on training adaptations. Evidence suggests that adaptations to training are due to changes in the types and activities of various proteins in response to each exercise bout. Thus, study of the acute metabolic and molecular responses to exercise plus nutrition may provide valuable information about the expected influence on training adaptations. The type of protein, timing of protein ingestion relative to exercise, concurrent ingestion of other nutrients with protein, as well as the type of exercise training performed will impact the adaptations to training with the intake of protein. Protein is an important nutrient for muscle hypertrophy with training, but there is little support for the need for very high (e.g. >2.5-3.0 grams of protein per kilogram of body weight) intakes. Traditionally, endurance athletes have focused on carbohydrate intake, but recently protein has been touted to be critical during and after endurance exercise. There is evidence for and against the importance of protein for endurance exercise and more, well-controlled studies are required to delineate the importance of protein for endurance exercise adaptations. Whereas nutritional manipulations have customarily been focused on preventing protein degradation, muscle damage, and oxidative stress, recent evidence suggests that these processes may be critical for the optimal adaptive response to training.